Peritonitis caused by Listeria monocytogenes and Burkholderia cepacia in a patient on peritoneal dialysis: a case report - Tsai, Yu-Chi; Tsai, Ming-Kai; Kung, Wen-Ching; Wang, Chien-Yao (Frontiers in Medicine, 2024)
Peritoneal dialysis (PD)-associated peritonitis is a major cause of peritoneal dysfunction and failure. The main issue regarding the treatment is whether to remove the catheter surgically or to treat with antibiotics alone. Notably, PD-associated peritonitis is commonly caused by gram-positive cocci, but rarely by Listeria monocytogenes and Burkholderia cepacia. Here, we report a patient diagnosed with PD-associated peritonitis caused by L. monocytogenes and B. cepacia who presented with a fever, abdominal pain, and turbid dialysate and had been receiving PD for over 20 years. After 2 weeks of antibiotic treatment, the catheter in the patient was surgically removed. Culture and pathology results revealed pathogen growth, foreign body granuloma with chronic inflammation, and inflammatory cells with fibroblast infiltration. The patient was switched to hemodialysis. She eventually recovered and was discharged. The patient presented fair health at the 3-month follow-up. In conclusion, sequential dialysate white blood cell count may help clinicians decide the course of treatment and guide the timing of surgical intervention.